1987
DOI: 10.1152/ajpregu.1987.252.2.r240
|View full text |Cite
|
Sign up to set email alerts
|

Fragility and composition of growing rat bone after one week in spaceflight

Abstract: To gain some insight into the early effects of spaceflight on skeletal metabolism, we quantified the major chemical constituents and a noncollagenous protein, osteocalcin, in the third-lumbar vertebrae and humeri from 8-wk-old rats that were part of the 7-day NASA Spacelab 3 flight experiments. The ratio of calcium to hydroxyproline in the humeral diaphysis increased from 8.5 in preflight to 9.8 in ground simulation control and only to 8.9 in flight bones. There was no demonstrable change in the fraction of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 0 publications
1
25
1
Order By: Relevance
“…A significant reduction in serum testosterone levels was previously reported in 12-day tail-suspended rats (45,47,48) and in rats flown in the 14-day Cosmos 2014 mission (30). Tail suspension, disuse of limbs, and exposure to microgravity significantly decrease bone formation and can consequently decrease BMD in rats (14,19,29,34,49). Testosterone and anabolic steroids have positive effects on osteoblasts cells in bone formation (21).…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…A significant reduction in serum testosterone levels was previously reported in 12-day tail-suspended rats (45,47,48) and in rats flown in the 14-day Cosmos 2014 mission (30). Tail suspension, disuse of limbs, and exposure to microgravity significantly decrease bone formation and can consequently decrease BMD in rats (14,19,29,34,49). Testosterone and anabolic steroids have positive effects on osteoblasts cells in bone formation (21).…”
Section: Discussionmentioning
confidence: 60%
“…Over the past few years, several countermeasures have been examined to prevent the loss of musculoskeletal mass during exposure to microgravity. These include pharmacological therapies, such as calcitonin and bisphosphonates, and several active and passive exercise regimens, but the outcomes have been limited.The hindlimb-elevation model in rats has been shown to simulate the bone turnover and muscle changes seen in growing rats in spaceflight (18,19,34). This model mimics the effects of microgravity on musculoskeletal systems, metabolic changes affecting bone formation, renal function, electrolyte disturbances, and muscle mass as compared with those recorded from biosatellite animals.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Diminished osteoblast function is a critical factor in the bone loss that develops in weightlessness. Biochemical studies of astronauts in space (diminished serum osteocalcin levels) and studies of animals both before and after space flight or simulated weightless states provide evidence for diminished osteoblast function [3]. Studies have shown that there is a decrease in osteoblast number and activity after space flight [4].…”
mentioning
confidence: 99%